2010
DOI: 10.1038/aps.2010.39
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of self-renewal of embryonic stem cells by midkine

Abstract: Aim: To characterize the expression and function of midkine (MK) in an in vitro embryonic stem cell (ESC) culture system. Methods: To investigate the potential roles of MK, the expression of MK in ESCs was evaluated by RT-PCR and immunocytochemistry. The effects of MK on the self-renewal of ESCs were measured using alkaline phosphatase assays, immunocytochemistry, RT-PCR and colony-forming assays. The mechanism of the growth-promoting effect of MK in mESCs was assessed by cell cycle analysis and Western blot a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 41 publications
(46 reference statements)
1
21
0
Order By: Relevance
“…Equal amounts of RNA were reverse transcribed into cDNA using oligo(dT) 15 primers. The primer sequences used were: mouse IFN-β sense 5′-CTT CTC CAC CAC AGC CCT CTC-3′, anti-sense 5′-CCC ACG TCA ATC CTT TCC TCT T-3′ [13]; mouse β-actin sense 5′-TGG AAT CCT GTG GCA TCC ATG AAA C-3′, anti-sense 5′-TAA AAC GCA GCT CAG TAA CAG TCC G-3′ [14]. iQ ™ SYBR® Green Supermix (Bio-Rad Laboratories, Inc., Hercules, CA, USA) and iCycler iQ ™ Real-time PCR Detection System (Bio-Rad Laboratories, Inc.) were used for real-time PCR analysis.…”
Section: Quantification Of Ifn-β Mrnamentioning
confidence: 99%
“…Equal amounts of RNA were reverse transcribed into cDNA using oligo(dT) 15 primers. The primer sequences used were: mouse IFN-β sense 5′-CTT CTC CAC CAC AGC CCT CTC-3′, anti-sense 5′-CCC ACG TCA ATC CTT TCC TCT T-3′ [13]; mouse β-actin sense 5′-TGG AAT CCT GTG GCA TCC ATG AAA C-3′, anti-sense 5′-TAA AAC GCA GCT CAG TAA CAG TCC G-3′ [14]. iQ ™ SYBR® Green Supermix (Bio-Rad Laboratories, Inc., Hercules, CA, USA) and iCycler iQ ™ Real-time PCR Detection System (Bio-Rad Laboratories, Inc.) were used for real-time PCR analysis.…”
Section: Quantification Of Ifn-β Mrnamentioning
confidence: 99%
“…Recent studies indicate that cancer stem cells share core signaling pathways with normal somatic or embryonic stem cells, but also display critical distinctions that provide important clues into useful therapeutic targets. High MDK levels also plays critical role in this distinction (Yao et al, 2010). These are very highly infiltrative cancers often invade into normal brain tissues preventing surgical resection, and GSCs are responsible for this aggressive invasive phenotype, so targeting GSCs can effectively reduce tumor resistance and recurrence.…”
Section: Concluding Remarks and Discussionmentioning
confidence: 99%
“…Thus, we can conclude that drug efflux ability was not correlated with MDK levels in this experiment. Yao and coworkers revealed that MDK is expressed in mouse embryonic stem cells (mESCs), human embryonic stem cells (hESCs) and mouse embryonic fibroblasts (MEFs) (Yao et al, 2010). In their study, MDK promotes proliferation and self-renewal of both mESCs and hESCs.…”
Section: Midkine and Glioblastomamentioning
confidence: 99%
“…54) In the presence of MK, the MAPK and PI3K/AKT pathways participate in injured tissues recovery process, like the recovery of ischemic myocardial injury, [23][24][25][26][27] cartilage trauma [89][90][91] and amphetamine-induced neurotoxicity. 92) MAPK and PI3K/AKT pathways also take part in the proliferation and self-renewal of stem cells, like embryonic stem cells (ES) 20) and hematopoietic stem cell (HSC) after stimulation by PTN. 21,22) Janus Tyrosine Kinase (JAK)/Signal Transducer and Activator of Transcription (STAT) Pathway In human G401 cells, MK but not PTN activates JAK/STAT pathway through a protein or a protein complex whose molecular weight is about 200 kDa.…”
Section: )mentioning
confidence: 99%
“…chemo-taxis of macrophages and neutrophils) which leads to vascular restenosis, interstitial nephritis, renal injury and rheumatoid arthritis. 19) At present, the involvement of MK and PTN in stem cell proliferation and renewal [20][21][22] further highlight their potential as regenerative therapeutics. For example, MK has been demonstrated to promote the recovery of ischemic injury in the heart and brain, [23][24][25][26][27][28] attenuate the deposition of amyloid β-peptide plaques and progression of Alzheimer's disease, 29) facilitate liver regeneration 30) as well as aid in the repair of bone fracture and muscle injury.…”
Section: Introductionmentioning
confidence: 99%